A Glance at Work Educational Perspectives - Boffo, Vanna (Strumenti per la didattica e la ricerca, 2012)
The topics of work flexibility, precarious jobs, and the relationship between work, the market and production are subjects that are widely debated in the sociological, philosophical, economic and political spheres. Yet these topics are less touched on in the tradition of pedagogical research. The intention of this book is to build a seedbed for reflection on the central position assumed by work in the lives of every woman and man, inhabitants of a planet in which the transformation of work activities is imposing radical changes on lifestyles, community-building and societies. Work is not an abstract concept, but is incorporated into every human person who does it and into the relationships linking them to others. Man, his education and human formation provide the pivot around which to perform a pedagogical survey within the universe of "work", and inside the relationship between the human condition and working/professional life. What sense does work acquire today when going to observe children, young people, adults or migrants? Namely, what sense does it assume when its pivotal viewpoint is shifted off-centre in time and space? The essays intend to spark agile but critical, synchronic and diachronic reflection which, stemming from contextual questions on the meaning of work and on change in the workplace, will proceed to investigate the subjects in their specific lives and existential conditions. Essays by: Vanna Boffo, Pietro Causarano, Giovanna Del Gobbo, Emiliano Macinai, Maria Rita Mancaniello, Stefano Oliviero and Clara Silva.